Rapid formation of intense haze episodes via aerosol–boundary layer feedback in Beijing - Y. Wang; Y. Wang; M. Yu; Y. Wang; Y. Wang; G. Tang; T. Song; P. Zhou; Z. Liu; B. Hu; D. Ji; L. Wang; et al. (Atmospheric Chemistry and Physics, 2020)
Although much effort has been put into studying air pollution, our knowledge of the mechanisms of frequently occurring intense haze episodes in China is still limited. In this study, using 3 years of measurements of air pollutants at three different height levels on a 325 m Beijing meteorology tower, we found that a positive aerosol–boundary layer feedback mechanism existed at three vertical observation heights during intense haze polluted periods within the mixing layer. This feedback was characterized by a higher loading of PM2.5 with a shallower mixing layer. Modelling results indicated that the presence of PM2.5 within the boundary layer led to reduced surface temperature, relative humidity and mixing layer height during an intensive haze episode. Measurements showed that the aerosol–boundary layer feedback was related to the decrease in solar radiation, turbulent kinetic energy and thereby suppression of the mixing layer. The feedback mechanism can explain the rapid formation of intense haze episodes to some extent, and we suggest that the detailed feedback mechanism warrants further investigation from both model simulations and field observations.